ADDING TIME AND LEVELS OF DETAIL IN THE BUILDINGS MODEL - Tuan Anh, Nguyen Gia (Vietnam Journal of Science and Technology, 2012)
ABSTRACTThe paper describes two improvements in the available three-dimensional (3D) data model-Urban Data Model (UDM) with surface and body objects. The advantages of these improvements reduce size of data storage; reduce the time cost of data show and visualizing data more realistic than the original model. The paper also added to the model time class to manage historical of changes on the spatial properties of  1D, 2D and 3D object. The levels of detail added to show buildings at four levels from simple to complex. Event class in the model should record the reasons to create changes on the buildings in their evolution.Keywords.  3D, data model, spatio-temporal model.